Current Trends and Tendencies in Field Didactics - Janík, Tomáš; Stuchlíková, Iva (Scientia in educatione, 2013)
This review paper focuses on current developments in didactics. Firstly, key terms are defined — general didactics, inter-subject didactics, field didactics, and subject didactics. On the basis of these definitions, the most important didactic traditions and conceptions are introduced that are being developed in different cultural regions (German, Scandinavian, French, Anglo-American and others). Secondly, two important stimuli for the independence and development of field didactics are described — professionalization-based and curricular. In the second part of the paper, the focus lies on natural sciences field didactics. Trends in natural sciences field didactics are discussed as well as sources of inspiration in the field didactics for other fields. Towards the end of the paper, perspectives for further development of didactics and field didactics in the Czech Republic are outlined. A critical analysis of these perspectives implies a rise of didactics; at least in the continental Europe, where it has a long and respected tradition.